Dasar Teoritis Dan Filosofis Perbankan Syariah Di Indonesia Dalam Sistem Ekonomi Syariah - Sobarna, Nanang; Purwanti, Neli (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Islamic banking in Indonesia is part of the Islamic economic system that operates based on Islamic principles, guided by a business philosophy derived from the Qur'an and Hadith, by implementing the principle of fair profit sharing for all parties. This study aims to examine the theoretical and philosophical basis of Islamic banking in Indonesia in the Islamic economic system. This research method is carried out with a qualitative approach, namely research that produces information in the form of descriptive notes contained in the text being studied. The results of the discussion show that Islamic banking is everything related to Islamic banks whose operations are based on Islamic principles both in fundraising products, in financing distribution both with the principles of buying and selling, profit sharing, and leasing, as well as in Islamic bank service products and social service products. From a philosophical perspective, Islamic banking in Indonesia in the Islamic economic system is in accordance with Pancasila, the 1945 Constitution and the Qur'an-Hadith as sources of Islamic principles.